Grapevine Pathogenic Microorganisms: Understanding Infection Strategies and Host Response Scenarios - Armijo, Grace; Schlechter, Rudolf; Agurto, Mario; Muñoz, Daniela; Nuñez, Constanza; Arce-Johnson, Patricio (Frontiers in Plant Science, 2016)
Grapevine (Vitis vinifera L.) is one of the most important fruit crop worldwide. Commercial cultivars are greatly affected by a large number of pathogenic microorganisms that cause diseases during pre- and/or post-harvest periods, affecting production, processing and export, along with fruit quality. Among the potential threats, we can find bacteria, fungi, oomycete, or viruses with different life cycles, infection mechanisms and evasion strategies. While plant–pathogen interactions are cycles of resistance and susceptibility, resistance traits from natural resources are selected and may be used for breeding purposes and for a sustainable agriculture. In this context, here we summarize some of the most important diseases affecting V. vinifera together with their causal agents. The aim of this work is to bring a comprehensive review of the infection strategies deployed by significant types of pathogens while understanding the host response in both resistance and susceptibility scenarios. New approaches being used to uncover grapevine status during biotic stresses and scientific-based procedures needed to control plant diseases and crop protection are also addressed.